Extralobar pulmonary sequestration with combined gastric and intradiaphragmatic locations. Issue 5 (10th September 2013) - Chouikh, Taieb; Berteloot, Laureline; Revillon, Yann; Delacourt, Christophe; Khen‐Dunlop, Naziha
Summary Extralobar pulmonary sequestration is a congenital lung malformation characterized by a non‐functional lung segment with systemic feeding vessel. Over 90% of sequestrations are found in the thorax with less than 10% located in the abdomen. We present an unusual case of intra abdominal pulmonary sequestration, located suprarenally, adherent to both the stomach and the diaphragm. The malformation was surgically excised via laparoscopy in the second year of life, when no evidence of regression was found on follow up imaging. On the occasion of this description, the spectrum of bronchopulmonary foregut malformation is discussed. Pediatr Pulmonol. 2014; 49:512–514. © 2013 Wiley Periodicals, Inc.